Beta-lactam combination therapy for the treatment of Staphylococcus aureus and Enterococcus species bacteremia: A summary and appraisal of the evidence. (October 2017) - Bartash, Rachel; Nori, Priya
Highlights: Staphylococcus aureus bacteremia and Enterococcus species bacteremia have high mortality. There is interest in combination therapy with at least one beta-lactam antibiotic. In vitro data are favorable, but clinical data for combination regimens are limited. Combination therapy with at least one beta-lactam may be useful in refractory cases. Further studies are needed to investigate the safety and efficacy of each regimen. Abstract: Staphylococcal bacteremia and enterococcal bacteremia are prevalent in hospitalized or recently instrumented patients, and are associated with significant morbidity and mortality. They are often difficult to treat due to the pathogenicity of the organisms, poor response to antibiotics, and increasing development of multidrug resistance. Therefore, there has been increasing interest in combination therapy for the treatment of these infections. The aim of this review was to summarize and assess the evidence supporting combination beta-lactam therapy for both Staphylococcus aureus and Enterococcus species blood stream infections. Currently, there is promising in vitro data but little clinical evidence supporting combination beta-lactam therapy for this indication. Further clinical investigations are needed to elucidate the potential benefits of beta-lactam combination therapy over monotherapy for Gram-positive bacteremia, although combination therapy may be useful in refractory cases of bacteremia that do not respond to standard antibiotic therapy.